Peramalan Penerbitan Ijin Mendirikan Bangunan Dengan Single Moving Average Dan Exponential Smoothing - Pramana, Yogha; Hartati, Rukmi Sari; Oka Saputra, Komang (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi Elektro, 2019)
Building Construction Permits are permits granted by the Regional Head to building owners to build new, change, expand, reduce or maintain buildings in accordance with administrative requirements and applicable technical requirements. Forecasting is an estimate or estimate of the occurrence of an event or event in the future. Forecasting is an important tool in efficient and effective planning. The process is to estimate what future needs include needs in terms of quantity, quality, time and location needed to fulfill the demand for goods or services. Forecasting is the initial part of a decision making process. Data for Building Construction Permits (IMB) was calculated using the Simple Moving Average and Exponential Smoothing method to determine the value of Mean Error, Mean Absolute Deviation, Mean Square Error, Standard Error, Mean Absolute Percent Error.